2022
DOI: 10.48550/arxiv.2201.12967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the superconducting instability in a two-orbital $d$-$s$ model: insights to infinite-layer nickelate superconductors

Abstract: Motivated by the recent realization of the infinite-layer nickelate superconductivity (SC), we quantitatively investigate a two-orbital d-s model by dynamic cluster quantum Monte Carlo calculations. Focusing on the impact of inter-orbital hybridization on the superconducting properties, our simulations indicate that the d-s hybridization strength has a decisive role in the suppression of the d-wave pairing in the doping regime relevant to infinite-layer nickelates. Although we confirm on the single-orbital des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…[115] They found that d x 2 −y 2 Cooper pairing is a prominent candidate SC state, which is in line with earlier literatures. [116][117][118][119][120][121] However, a transition from d x 2 −y 2 wave to nodal s ± wave and even a triplet p z state (Figure 18a) occurs with the strengthening of electronic correlations. The orbital-resolved DOSs for the three pairing symmetries are shown in Figure 18b.…”
Section: Orbital Physics Electronic Structures and Pairing Symmetriesmentioning
confidence: 99%
“…[115] They found that d x 2 −y 2 Cooper pairing is a prominent candidate SC state, which is in line with earlier literatures. [116][117][118][119][120][121] However, a transition from d x 2 −y 2 wave to nodal s ± wave and even a triplet p z state (Figure 18a) occurs with the strengthening of electronic correlations. The orbital-resolved DOSs for the three pairing symmetries are shown in Figure 18b.…”
Section: Orbital Physics Electronic Structures and Pairing Symmetriesmentioning
confidence: 99%
“…High-temperature superconductivity in Nd 1-x Sr x NiO 2 was experimentally discovered by Li et al [ 1 ] in 2019, while the first theoretical report in which the oxidation state of Ni + was established to be a condition under which nickelates become similar to cuprates (created by Li et al [ 1 ]) was published by Anisimov et al [ 2 ] in 1999. This experimental discovery initiated further theoretical and experimental studies on R 1-x A x NiO 2 (where R is a rare earth and A = Sr, Ca) thin films [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , ...…”
Section: Introductionmentioning
confidence: 99%
“…This experimental discovery initiated further theoretical and experimental studies on R 1-x A x NiO 2 (where R is a rare earth and A = Sr, Ca) thin films [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] and bulk [ 51 ]. It is a widely accepted point of view that the superconducting state in nickelates is exhibited only in thin films [ 2 , 3 , 4 , …”
Section: Introductionmentioning
confidence: 99%
“…The main debate is between moderately-to-strongly correlated Ni-d x 2 −y 2 -driven physics, and multi-orbital Ni(3d) mechanisms [24,25]. In the former case, SC nickelates are described as cuprate-like with a dominant d x 2 −y 2 -wave SC pairing [21,[26][27][28][29][30][31][32]. If additional SD-driven Kondo correlations are taken into account, other intriguing d-wave and also s-wave pairing solutions may become stabilized [33].…”
mentioning
confidence: 99%